Beating asthma through education. Issue 7 (July 2021) - McLellan, Elizabeth; Townshend, Jennifer; Hails, Sally; De Zwart, Patty; Levey, Ruth; Moss, Samantha
Abstract: Asthma is a common, chronic respiratory disease which affects 1 in 11 children within the UK. The National Review of Asthma Deaths (NRAD) highlighted common and avoidable factors contributing to the deaths and made recommendations for care. The team at the Great North Children's Hospital (GNCH) recognized a need for change, which led to the development of a new educational programme. BeatAsthma was co-designed with stakeholders. It comprises over 170 resources available for use in primary, secondary and tertiary care. This article briefly describes our experience and some of the materials available and the early results of this intervention.